Evidence for Progressive Cognitive Deficits in Patients With Major Depressive Disorder - Liu, Jin; Liu, Bangshan; Wang, Mi; Ju, Yumeng; Dong, Qiangli; Lu, Xiaowen; Sun, Jinrong; Zhang, Liang; Guo, Hua; Zhao, Futao; Li, Weihui; Zhang, Li; et al. (Frontiers in Psychiatry, 2021)
Background: Cognitive deficits have been shown to be progressive in major depressive disorder (MDD). However, it remains unknown which component of cognitive function is progressive impaired across episodes of MDD. Herein we aimed at identifying the progressive impaired cognitive components in MDD. Methods: A comprehensive neurocognitive test battery was used to assess the cognitive components (executive function, attention, processing speed, memory, working memory, inhibition, shifting, and verbal fluency) in 35 patients with first-episode MDD (FED), 60 patients with recurrent MDD (RD) and 111 matched healthy controls (HCs). After 6 months of antidepressant treatment, 20 FED and 36 RD patients achieved clinical remission and completed the second-time neurocognitive test. Statistical analyses were conducted to identify the impaired cognitive components in FED and RD groups before and after treatment; and to assess the relationships between cognitive components and number of episodes and total illness duration in the total MDD group. Results: At baseline, both the FED and RD groups showed impairments in all of the cognitive components; FED and RD groups showed no significant difference in all of the components except for shifting. After remission, only shifting in RD group showed no significant improvement and remained impaired. Furthermore, shifting was the only component negatively correlated with number of episodes and total illness duration. Conclusions: Shifting may serve as the progressive cognitive deficit across episodes of MDD.